The effects of the EquiAmiTM training aid on the kinematics of the horse at the walk and trot In-Hand - Calzone, S.; Wilkins, C.; Deckers, I.; Nankervis, K. (Journal of Equine Veterinary Science, 2022)
The EquiAmi Training Aid (ETA) is a popular training and rehabilitation tool, however knowledge about its effect on the equine gait is lacking. Understanding of its effects on equine kinematics, and the clinical relevance of these effects is vital to promote optimal use of training aids within training and rehabilitation programmes. Therefore, this study aimed to determine how the ETA influences horses` gait kinematics at walk and trot. Eight horses walked and trotted in-hand with and without the ETA. Optical motion capture was used to measure forelimb and hindlimb pro- and retraction angles, withers-croup angle, and stride length. Separate repeated-measures ANOVAs in each gait were used to assess the differences between gait kinematics and stride length variability with and without the ETA. The ETA did not significantly influence the horses` kinematics in walk or trot, however, individual differences in the effect of the ETA on the horses` angular and linear kinematics were found, with variation between gaits within the same horse observed. The ETA does not have the same effect on every horse, and its effect can vary within the same horse between gaits. Therefore, the individual characteristics and needs of the horse must be considered when applying training aids.